Implementing Statistical Process Control (SPC) In The Transformation of Trimming II Process - Indriyati K, Retno; Hendra, Franka; Effendi, Riki; Sirait, Morhan; Hutasoit, Jisman; Alviansyah, Dede (Suara Teknik : Jurnal Ilmiah, 2023)
The The main objective of this study is to analyze the implementation of quality control in the process, types of defects, and factors that cause defects in the Trimming II process and improve product quality. The method used is the Statistical Process Control (SPC) method with control aids (cheeksheet, Pareto diagram, histogram, cause and effect diagram, and control chart, scatter. The results of the study using the seven tools method found 4 types of defects in the Trimming II process defects such as scratched rear panels, crooked cross shaft frame, blower unfunction, and loose horn bracket bolts. The results of histogram diagram analysis for the highest type of defect are bolt bracket horn types the horn bracket bolts) are loose by 548. The results of the analysis of the Pareto diagram for the type of defect of the horn bracket bolts are loose by 34.6%. meaning it is still not under control. Based on the cause effect diagram and the causative factors of the type ca loose horn bracket bolts analyzed using the 5W+1H method, namely fatigue and inaccuracy at work, employee experience and understanding, dirty smelly material, difference in bolt size, disturbing noise, dusty production line conditions, hot production line temperature conditions.